A Reinvestigation of Coalescence Reactions of Fullerenes - Shumei Yang; Jicheng Yang; Jinyang Li; Guanxin Yao; Xianyi Zhang; Xianglei Kong (Inorganics)
Gas-phase studies of fullerenes and metallofullerenes, though less well explored compared to condensed-phase research in recent years, offer critical insights into the mechanisms governing their formation and behavior. In this study, we re-examined the coalescence reactions of fullerenes using a high-resolution Fourier transform ion cyclotron resonance (FT ICR) mass spectrometer, especially the effect of electric fields in the source region on the formation of large-sized fullerenes. By varying the voltages on the metal plate where the C60 was deposited, we achieved enhanced control over the coalescence process, revealing distinct distributions of fullerene products that differ from those reported in earlier studies. What is the most attractive is that a negative voltage applied on the metal plate is actually more conducive to the production of large-sized fullerene cations. Notably, we identified previously unobserved species, including doubly charged fullerene cations (e.g., C1602+) and metallofullerene ions (e.g., Y1–2C94–124+), providing new evidence for the complexity of gas-phase fullerene chemistry. These findings underscore the importance of source region electric fields in shaping coalescence outcomes and highlight the potential of gas-phase approaches for synthesizing novel metallofullerenes.